2021
DOI: 10.21203/rs.3.rs-145189/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generative Capacity of Probabilistic Protein Sequence Models

Abstract: Potts models and variational autoencoders (VAEs) have recently gained popularity as generative protein sequence models (GPSMs) to explore fitness landscapes and predict the effect of mutations. Despite encouraging results, quantitative characterization and comparison of GPSM-generated probability distributions is still lacking. It is currently unclear whether GPSMs can faithfully reproduce the complex multi-residue mutation patterns observed in natural sequences arising due to epistasis. We develop a set of se… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…We especially thank Francisco McGee and Vincenzo Carnevale for providing generated samples from DeepSequence as in ref. 34 . Our work was partially funded by the EU H2020 Research and Innovation Programme MSCA-RISE-2016 under Grant Agreement No.…”
Section: Acknowledgementsmentioning
confidence: 99%
See 4 more Smart Citations
“…We especially thank Francisco McGee and Vincenzo Carnevale for providing generated samples from DeepSequence as in ref. 34 . Our work was partially funded by the EU H2020 Research and Innovation Programme MSCA-RISE-2016 under Grant Agreement No.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…It currently provides one of the best mutational-effect predictors, and we will show below that arDCA provides comparable quality of prediction for this specific task. The DeepSequence code has been modified in 34 to explore its capacities in generating artificial sequences being statistically indistinguishable from the natural MSA; it was shown that its performance was substantially less accurate than bmDCA. Another implementation of a VAE was reported in 35 ; also in this case the generative performances are inferior to bmDCA, but the organization of latent variables was shown to carry significant information on functionality.…”
mentioning
confidence: 99%
See 3 more Smart Citations